PENGARUH TEKNIK REBOZO TERHADAP PENURUNAN NYERI PERSALINAN ( EVIDENCE BASED CASE REPORT): The Effect of Rebozo Technique on Reducing Labor Pain - Anggraeni Dewi, Rinye (Jurnal Kesehatan Siliwangi, 2024)
Background: Labor pain will affect discomfort physical and psychological conditions and labor process will interfere if not handled properly. In the labor when cervical dilation occurs, the greater the cervical dilation, the more frequent and painful the pain felt by the mother. Purpose: To reduce the use of drugs or pharmacological therapy, an intervention is carried out in the form of a non-pharmacological method using the rebozo technique. Method: This method uses the Evidence Based Case Report (EBCR). The article search was carried out using the PubMed, Google Scholar and Cochrane Library databases. The keywords used are appropriate and represent the population, rebozo technique, pain labor, pain relief and childbirth. The search for articles is limited and published in the last 10 years, articles with full text. 3 articles were obtained for use. Respondents will be measured for pain levels using the Numeric Rating Scale (NRS) and the Wong Baker Face Pain Rating Scale. Result: Before the intervention, the pain level was 6-7 with the severe pain category and after the intervention, the pain level was 4-5 with the moderate pain category. Conclusion: Rebozo technique intervention to reduce labor pain and delivery’s progress had a good effect.